Bone Defect Animal Model for Hybrid Polymer Matrix Nano Composite as Bone Substitute Biomaterials - Kashan, Jenan S.; Hamdan, Wisam K.; Fakhri, Baha (Al-Khwarizmi Engineering Journal, 2018)
Addition of bioactive materials such as Titanium oxide (TiO2), and incorporation of bio inert ceramic such as alumina (Al2O3), into polyetheretherketone (PEEK) has been adopted as an effective approach to improve bone-implant interfaces. In this paper, hot pressing technique has been adopted as a production method. This technique gave a homogenous distribution of the additive materials in the proposed composite biomaterial. Different compositions and compounding temperatures have been applied to all samples. Mechanical properties and animal model have been studied in all different production conditions. The results of these new TiO2/Al2O3/PEEK biocomposites with different compositions were promising, mechanical properties within the range of human cortical bone, suitable for load bearing applications. At the same time, in vivo test shows no inflammation reaction with implanted samples. Sustained viability in contact with the sample over seven-day period, showed evidence of excellent biocompatibility in injured rejoins.